2018
DOI: 10.1007/s00526-018-1368-0
|View full text |Cite
|
Sign up to set email alerts
|

Design of lattice surface energies

Abstract: We provide a general framework for the design of surface energies on lattices. We prove sharp bounds for the homogenization of discrete systems describing mixtures of ferromagnetic interactions by constructing optimal microgeometries, and we prove a localization principle which allows to reduce to the periodic setting in the general nonperiodic case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Indeed, example 2.8 shows that for infinite range interactions this is in general not true. In [15,16] it is shown that, as the periodicity T of the interactions tends to +∞, it is possible to approximate any norm as surface energy density satisfying suitable growth conditions. We refer to [2] for a random setting where it is shown that an isotropic energy density (and thus non-crystalline) can be obtained in the limit.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, example 2.8 shows that for infinite range interactions this is in general not true. In [15,16] it is shown that, as the periodicity T of the interactions tends to +∞, it is possible to approximate any norm as surface energy density satisfying suitable growth conditions. We refer to [2] for a random setting where it is shown that an isotropic energy density (and thus non-crystalline) can be obtained in the limit.…”
Section: Introductionmentioning
confidence: 99%
“…where Q ν is the square with one side orthogonal to ν, u pos ε and u neg ε are the ground states depicted in Figure 1, and ∂ ± ε Q ν are a discrete version of the top/bottom parts of ∂Q ν . Asymptotic formulas like (1.3) are common in discrete-to-continuum variational analyses and are often used to represent Γ-limits of discrete energies [6,10,13,12,8,29]. However, proving an asymptotic lower bound with the density (1.3) for this model requires additional care and is the technically most demanding contribution of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…For N fixed, the physical system is expected to behave like a classical Ising-type system with N phases. (See also [16,1,3,15,2,19,11,13,18,14] for the analysis of spin systems in the surface scaling.) According to the results proven for the Ising system, we expect the limit energy to be finite on functions of bounded variation with values in the finite set S N .…”
Section: Introductionmentioning
confidence: 99%